Endothelial dysfunction in femoral artery of the hypertensive rats is nitric oxide independent - Púzserová, A; Kopincová, J; Slezák, P; Bališ, P; Bernátová, I (Physiological research, 2013)
This study examined nitric oxide (NO) production, oxidative load and endothelium-dependent relaxation (NO-dependent and NO-independent) in adult male borderline hypertensive (BHR) and spontaneously hypertensive (SHR) rats as compared to normotensive Wistar-Kyoto (WKY) rats. Systolic blood pressure (BP) was determined by tail-cuff. NO production was determined by conversion of [(3)H]-L-arginine. Conjugated dienes (CD) and concentrations of thiobarbituric acid-reactive substances (TBARS) were measured for assessment of oxidative load. Vascular function was investigated in rings of the femoral artery (FA) using a wire myograph. BP of WKY, BHR and SHR was 106+/-2, 143+/-3 and 191+/-3 mm Hg, respectively (p<0.01 for each). Significant left ventricle (LV) hypertrophy and elevated levels of CD and TBARS in the LV were present in BHR and SHR as compared to WKY. NO production was elevated significantly in the aorta of BHR and SHR vs. WKY as well as in the LV of SHR vs. WKY. Acetylcholine (ACh)-induced relaxation of the FA was reduced significantly in both BHR and SHR vs. WKY. The NO-dependent component of ACh-induced relaxation had increasing tendency in hypertensive groups and it correlated positively with BP. The NO-independent component of vasorelaxation was reduced significantly in BHR and SHR vs. WKY and it correlated negatively with BP. In conclusion, the results showed that endothelial dysfunction in the experimental model of borderline hypertensive and hypertensive rats is NO-independent. The results suggest that borderline hypertension represents a risk of other cardiovascular disorders which is qualitatively similar to that of fully developed hypertension.
Keywords: Rats; krevní tlak; tuhost cévní stěny; Endothelium, Vascular; Hypertension; mužské pohlaví; potkani inbrední SHR; Vascular Stiffness; krysa rodu Rattus; onemocnění periferních arterií; zvířata; Blood Pressure; oxid dusnatý; Nitric Oxide; hypertenze; Rats, Inbred WKY; cévní endotel; Peripheral Arterial Disease; Femoral Artery; Rats, Inbred SHR; arteria femoralis; potkani inbrední WKY; Male; Animals